Meta-analysis: A Tool for Upgrading Inputs of Macroeconomic Policy Models - Raymond J.G.M. Florax; Henri L.F. de Groot; Ruud A. de Mooij (Tinbergen Institute, 2002)
Meta-analysis is a research method to synthesise previously obtained researchresults. It is best seen as a statistical approach towards reviewing and summarising theliterature. This paper aims to introduce and critically review the research method ofmeta-analysis and to illustrate its potential use in applied economic policy analysis.Special attention will be paid to the possibilities for value transfer and thepossibilities to improve the calibration of existing macroeconomic policy models.
Keywords: B40; C80; 330; meta-analysis; value transfer; research synthesis; Wirtschaftsforschung; Makroökonomik; Wissenschaftliche Methode; Theorie; Meta-Analyse